Self-Standing Graphene Sheets Prepared with Chemical Vapor Deposition and Chemical Etching - Odahara, Genki; Ishikawa, Tsuyoshi; Fukase, Kazuya; Otani, Shigeki; Oshima, Chuhei; Suzuki, Masahiko; Yasue, Tsuneo; Koshikawa, Takanori (IntechOpen, 2011)
None